(untitled) (Ozone Therapy Global Journal, 2022)
XII RUSSIAN SCIENTIFIC CONFERENCE IN OZONE-THERAPY V INTERNATIONAL JOINT CONFERENCE RUSSIAN-IMEOF Ozone: active forms of oxygen, nitric oxide, molecular hydrogen,and high-intensity physical factors in biology and medicine Nizhny Novgorod, October 14-15, 2021